Influence of PPA on the Short-Term Antiaging Performance of Asphalt - Lining Gao; Nana Cai; Xiaohong Fu; Rui He; Honggang Zhang; Jiayin Zhou; Dongliang Kuang; Shaowen Liu (Advances in Civil Engineering)
It has been confirmed that polyphosphoric acid (PPA) can significantly improve the high-temperature resistance, storage stability, and aging resistance of asphalt. The low price of PPA is conducive to the development of modified asphalt with high performance and excellent economy, suggesting its great application prospects. At present, there is little research on the role of PPA in delaying the aging process of PPA-modified asphalt, and a consensus has not yet been reached. Therefore, PPA-modified asphalt with different blending amounts (0 wt%, 0.4 wt%, 0.8 wt%, and 1.2 wt%) was prepared in this study. On the basis of variable performance, the role of PPA in the short-term antiaging process of asphalt is analyzed through Fourier transform infrared spectroscopy (FTIR) analysis of PPA-modified asphalt before and after aging, combined with the analysis of the change in components. The results showed that after PPA addition, the high-temperature resistance and the thermal stability of asphalt were improved and the temperature sensitivity was weakened. Both curves of ductility and G∗ indicate the potential saturation effect of PPA addition; together with infrared spectroscopy, we proved that there are both chemical reactions and physical mixing in the PPA-modified asphalt. The component fractions show that PPA will cause the asphalt to transform from sol to gel and the main function of PPA in retarding asphalt aging is the dispersion of the agglomerates of asphaltene micelles by PPA.